Demographic Characteristics and Inflammatory Biomarker Profile in Psoriatic Arthritis Patients with Comorbid Fibromyalgia: A Cross-Sectional Study - Marino Paroli; Chiara Gioia; Daniele Accapezzato; Rosalba Caccavale (Medicina, 2025)
Background and Objectives: Psoriatic arthritis (PsA) is a chronic rheumatic disease that is frequently associated with fibromyalgia (FM). The coexistence of FM complicates the evaluation of PsA disease activity and the planning of treatment strategies, as the two conditions share many overlapping clinical symptoms. To investigate the contribution of demographic factors and available serum biomarkers of inflammation and autoimmunity in characterizing the heterogeneity among patients meeting the classification criteria for both PsA and FM. Materials and Methods: This cross-sectional, single-center study involved 1547 adult patients evaluated between January 2017 and December 2024 who met the CASPAR criteria for PsA. A patient subgroup also met the 2016 ACR criteria for FM. Demographic data, serum inflammatory markers such as C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), and autoimmunity markers including antinuclear antibodies (ANA), rheumatoid factor (RF), and anti-citrullinated protein antibodies (ACPA) were evaluated. Statistical analyses included chi-square tests, t-tests, Mann–Whitney U tests, and multivariate logistic regression to identify independent predictors associated with the coexistence of PsA and FM. Results: A total of 254 patients (16.42%) were diagnosed with concomitant FM. Compared to patients with PsA alone, those with concurrent PsA and FM showed significantly lower C-reactive protein (CRP) levels (0.39 ± 0.74 vs. 2.88 ± 12.31 mg/dL; p < 0.001) and a higher frequency of antinuclear antibody (ANA) positivity (13.57% vs. 5.78%; p < 0.001). No significant differences were observed in rheumatoid factor (RF) or anti-citrullinated protein antibody (ACPA) positivity between the groups. Multivariate logistic regression identified female sex, ANA positivity, CRP levels ≤ 0.5 mg/dL, and elevated body mass index (BMI) as independent predictors of the presence of concomitant FM. Conclusions: Patients with concomitant PsA and FM have a distinct demographic and serological profile, suggesting the existence of a clinically significant subgroup within the PsA population. Recognition of these differences may improve diagnostic accuracy and support the development of personalized, non-immunosuppressive therapeutic strategies for this subgroup of patients.